Competitive advantages of farming enterprises in Ukraine: a methodic approach to diagnostics of the Added value of products : ст. - Lypchuk, V. (Scientific Papers Series Management, Economic Engineering in Agriculture and Rural Development, 2019)
The research sets the aim to argue theoretical fundamentals and outline the methods to make diagnostics of the added value of products, produced by farming enterprises. To determine reserves for improvement of competitive advantages of farming enterprises the work proposes to use an analytical instrument, called a “value chain”. The instrument helps to interpret production potential as a basis for the chain of values, which creates the added value. Applying the instrument, the research suggests that the structural indicators of the added value of farming enterprises demonstrate distortions, which are manifested in neutralization of a socially important element, i.e. labor payment, and in prevailing of a commercial constituent, i.e. profit. It is forced by inappropriate branch structure of large agricultural enterprises. Consequently, efficiency of the added value according to its reproductive capacity is higher at large farming enterprises, and according to the social focus – at family farms. It means that large farming enterprises have better reproductive capabilities and higher competitive advantages. At family farming enterprises of Ukraine, the added value can be increased and competitive advantage can be improved by means of valorization of their products basing on innovative activity. Such approach secures production focus on narrow markets and on specific needs of some individuals. It also creates preconditions for modernization, economic growth and improvement of competitive capacity of farming enterprises.
Keywords: farms; competitive; farming enterprises; фермерська конкуренція; ферми